4(x+2)-7(x-y)=7

Simple and best practice solution for 4(x+2)-7(x-y)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)-7(x-y)=7 equation:


Simplifying
4(x + 2) + -7(x + -1y) = 7

Reorder the terms:
4(2 + x) + -7(x + -1y) = 7
(2 * 4 + x * 4) + -7(x + -1y) = 7
(8 + 4x) + -7(x + -1y) = 7
8 + 4x + (x * -7 + -1y * -7) = 7
8 + 4x + (-7x + 7y) = 7

Combine like terms: 4x + -7x = -3x
8 + -3x + 7y = 7

Solving
8 + -3x + 7y = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -3x + -8 + 7y = 7 + -8

Reorder the terms:
8 + -8 + -3x + 7y = 7 + -8

Combine like terms: 8 + -8 = 0
0 + -3x + 7y = 7 + -8
-3x + 7y = 7 + -8

Combine like terms: 7 + -8 = -1
-3x + 7y = -1

Add '-7y' to each side of the equation.
-3x + 7y + -7y = -1 + -7y

Combine like terms: 7y + -7y = 0
-3x + 0 = -1 + -7y
-3x = -1 + -7y

Divide each side by '-3'.
x = 0.3333333333 + 2.333333333y

Simplifying
x = 0.3333333333 + 2.333333333y

See similar equations:

| (9x^8y^3)*1/2 | | 9y^2-144y=0 | | -12+3*(1-5)+(9-15)= | | 72= | | 9-y+2y=6 | | a+3b= | | 3y+2-4y=4 | | x+(x-50)+(x+30)=200 | | 9y^2-24x=0 | | 5x+2-3x=0 | | y-4y+2=14 | | 3x+4+9+x-2x-5= | | 26+2x=x+32 | | y+1(9+8)-28=21 | | 9m-3n-4m+10= | | 4a+8a-7a= | | 5g+7=90 | | (-112)-(-48)= | | (-48)-(-112)= | | 7+8=3x | | -6x-13/7= | | y=z/s | | 3.45=ln(1-n) | | 16t/8 | | 2t^2+2t-1=0 | | 3x+7+(-x)+-2=2x+5 | | 78(m+3)+m= | | ln5x/ln3x | | 0.05-320/x^2=0 | | 25m+7.25=443.75 | | dy/dx=(-2x)/y | | x(3x-2)=85 |

Equations solver categories